2007
DOI: 10.1158/0008-5472.can-06-4746
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Helicobacter pylori cagA Expression in Response to Salt

Abstract: Helicobacter pylori infection and a high dietary salt intake are risk factors for the development of gastric adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
119
3
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(130 citation statements)
references
References 46 publications
5
119
3
3
Order By: Relevance
“…We also observed that infection with 60190ΔcagA significantly reduced IL-8 induction, whereas 60190ΔcagE showed no induction at all. This is in agreement with previous results in which cagAmutants did not completely revert the induction of IL-8 but cagEmutants maintained basal IL-8 expression levels (29)(30)(31).…”
Section: Discussionsupporting
confidence: 93%
“…We also observed that infection with 60190ΔcagA significantly reduced IL-8 induction, whereas 60190ΔcagE showed no induction at all. This is in agreement with previous results in which cagAmutants did not completely revert the induction of IL-8 but cagEmutants maintained basal IL-8 expression levels (29)(30)(31).…”
Section: Discussionsupporting
confidence: 93%
“…Monomeric DprB and dimeric RuvC may differ in their affinity to differing DNA structures within bacterial cells. Microarray studies showed that dprB and ruvC have similar transcription levels in free-living H. pylori 26695 strains (44), suggesting that differences in function between the two proteins, rather than abundance, account for the differing phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with this, a recent study showed that elevated salt concentrations result in alterations in expression of the virulence factor CagA in H. pylori strain 26695 (16). Loh et al showed that an increased salt concentration slows H. pylori growth and affects expression of a large number of genes (16). Concomitant studies by our group that explored this effect in further detail are described here.…”
mentioning
confidence: 88%